A legal analysis of judicial rules and procedures relating to public order concept in Palestinian civil and commercial procedure law no. (2) of 2001 and the impact of nullity on it - Almashni, Mohammed Ibrahim Jamil (2022)
In Palestine, matters regarding civil and commercial disputes brought before civil courts are subject to the litigation procedures stipulated by the Palestinian Civil and Commercial Procedures Law No. 2 of 2001. According to this law, litigation rules are of two types: peremptory or supplementary rules, depending on their relevance to the public order concept. While the supplementary rules are subject to the will of the parties where they may agree to confer jurisdiction on a specific court located within the country of their choice, for peremptory rule that is related to public order, the jurisdiction belongs to the court. As specified in Law No. 2, the court and litigants must apply the peremptory rule, or judicial ruling will be nullified. Despite this, the Law does not clarify “public order”, making it impossible to distinguish peremptory rules and supplementary rules. Other than bringing about the nullity of the judgment, there were also inconsistencies and contradictions in the judicial decisions. Therefore, this study aims to examine public order concept in addition to distinguishing the peremptory rules from the supplementary rules. This is a doctrinal legal study that adopted a qualitative approach. The study considered both primary and secondary sources namely the law, scholarly articles, books, and online databases. Moreover, interviews were held with 12 respondents for their expert opinion on the subject matter where the data obtained were further transcribed. Other data sources gathered were critically and analytically analysed through the content analysis approach. The finding indicates uncertainty to the meaning and definition of public order concept that has caused difficulty in distinguishing peremptory and supplementary rules. This has not just resulted in contradictions and nullity of judicial rulings but also delaying the issuance of the judgments. Therefore, to avoid this ambiguity, the study recommends amending Law No. 2 by supplementing provisions that explain and clarify public order. This will subsequently enhance the concept of public order and make clear discrepancy between peremptory and supplementary rules, thus circumventing or lessening contradictions of judicial rulings and nullity of judgments.